Penerapan Model Pembelajaran Cooperative Learning Tipe STAD Media Card Sort dalam Meningkatkan Keaktifan Siswa pada Pelajaran Bahasa Arab di Madrasah Aliyah Darul Ulum Waru - azizah, cholifatul; Salwa Sabrina, Salwa; Maria Widya Wanti, Maria; Muhammad Ali Waffa, Waffa; Riyan Ashari, Riyan; Mufaizah, Mufaizah; Ahmad Marbuhin, Marbuhin (LP2M STAI Darul Kamal NW Kembang Kerang, 2025)
This study will look at the use of Card Sort media in the (STAD) Cooperative Learning paradigm to increase student engagement in Arabic language classes at MA Darul Ulum Waru. Arabic language subjects are also religious lessons, there needs to be activeness in them because students usually feel bored. The methodology used in this study is qualitative. Class X students who have difficulty understanding Arabic language material volunteered to be research subjects. Data were collected through observation and interviews. Interviews with students and one field supervisor who teaches Arabic. Then also see the results from when learning Arabic by implementing a different learning model, namely card sort. According to the study, the use of Card Sort media combined with the STAD learning approach significantly increases students' interest, activeness, and understanding of Arabic language subject matter and enthusiasm in learning. This increase can be seen from the way students participate in group discussions. Therefore, it is recommended that MA Darul Ulum Waru use this model to increase student activeness in learning Arabic. The uniqueness of the students is very enthusiastic, the interesting thing is that even though Arabic lessons can also use the card sort model, the importance of providing knowledge.